Method for preparing branched paraffin from polyolefin plastic

By using a physical mixing of solid superacid catalysts and polyethylene plastics, the dependence on precious metal catalysts and hydrogen in the prior art is solved, and efficient catalyzing the degradation of polyolefin plastics under low temperature conditions is achieved, and the selectivity of branched alkanes is improved.

CN119529871APending Publication Date: 2025-02-28EAST CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617910.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art relies heavily on precious metal catalysts and hydrogen in the process of preparing branched alkanes of polyolefin plastics, and the branched alkanes produced are relatively selective.

Method used

A solid system is used to physically mix solid super acid catalyst with polyethylene plastics to catalyze polyethylene degradation under low temperature conditions (260-320℃) through catalytic cracking reaction, thereby improving the selectivity of branched alkanes in gasoline products.

Benefits of technology

Without hydrogen or precious metals, efficient catalytic degradation of polyolefin plastics is achieved, and the yield of gasoline products (C4-C13) can reach 65%, and the selectivity of branched alkanes is as high as 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529871A_ABST
    Figure CN119529871A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plastic resource utilization, and discloses a method for preparing branched paraffin from polyolefin plastic. The method comprises the following steps: in an inert atmosphere, polyolefin plastic is subjected to a catalytic cracking reaction under the action of a catalyst, and the catalyst contains a mesoporous carrier and acid radical ions loaded on the mesoporous carrier. The solid superacid catalyst adopted by the method can stably exist in the air, is cheap and easy to synthesize, does not need the participation of co-reactants such as hydrogen and a solvent, has an adjustable structure and a suitable acid site, not only catalyzes the degradation of polyethylene under a low-temperature condition, but also greatly improves the selectivity of branched paraffin in a gasoline product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic resource utilization, and in particular to a method for preparing branched alkanes by utilizing polyolefin plastics. Background Art

[0002] Plastics are widely used synthetic polymer materials. As of 2017, global plastic production has surged to 8.3 billion tons and is expected to exceed 34 billion tons by 2050. Most plastics are made of polymers with a carbon-carbon backbone, and their environmental durability and low production cost have led to a large accumulation of plastic waste in landfills and natural environments. The rapid increase in plastic waste poses a threat to various ecosystems. Therefore, it is imperative to develop innovative chemical recycling and upgrading strategies for plastic waste. Polyethylene (PE) accounts for about 25% of global plastic production, but only a small amount of PE waste is recycled. Its thermal depolymerization process (e.g., pyrolysis or thermal cracking at above 400°C) involves complex reactions such as cracking, isomerization, hydrogenation, and aromatization, resulting in low selectivity for valuable products. In recent years, some leading strategies have successfully achieved the selective production of single products from polyolefins. For example, propylene is selectively produced by partial polyethylene dehydrogenation and ethylene metathesis reactions. Propylene is generated from polypropylene under far-from-equilibrium conditions using an electrified spatiotemporal heating method. Polyethylene is degraded to produce a single product, polyhydroxyalkanoate, through tandem chemical oxidation and biological funneling.

[0003] Branched alkanes are attractive target products, not only as the main components of gasoline, but also have a significant impact on its octane number. Conventional processes such as petroleum refining at high reaction temperatures (over 400°C) are generally less selective for branched alkanes. Polyethylene can be directly converted to liquid fuels at low temperatures by dehydrogenation, olefin metathesis, and hydrogenation at milder temperatures (less than 300°C) using organic iridium complexes and Re2O7 / γ-Al2O3 catalysts and solvents such as petroleum ether. However, this process mainly produces straight-chain alkanes. Polyolefins can be converted to alkanes by hydrogenolysis reactions carried out over noble metal catalysts in the presence of external hydrogen (200-250°C), however, the proportion of branched alkanes in the product is less than 40%, and methane is produced as a by-product. Although bifunctional metal / acid catalysts are attractive options for producing liquid fuels from polyethylene, their selectivity for branched alkanes requires excess hydrogen and noble metal catalysts. Therefore, there is an important impetus to develop efficient and stable catalysts to selectively convert polyethylene to branched alkanes. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of the prior art that in the process of preparing branched alkanes from polyolefin plastics, noble metal catalysts and hydrogen are heavily relied on, and the selectivity of generated branched alkanes is low. A method for preparing branched alkanes from polyolefin plastics is provided. The method adopts a solid-solid system in which a solid superacid catalyst is physically mixed with polyethylene plastic. The solid superacid catalyst can stably exist in the air, is cheap and easy to synthesize, does not require the participation of co-reactants such as hydrogen and solvents, has an adjustable structure and suitable acid sites, and not only catalyzes the degradation of polyethylene under low temperature conditions (260-320°C), but also greatly improves the selectivity of branched alkanes in gasoline products.

[0005] In order to achieve the above-mentioned object, the present invention provides a method for preparing branched alkanes using polyolefin plastics, the method comprising: subjecting the polyolefin plastics to a catalytic cracking reaction under the action of a catalyst under an inert atmosphere, wherein the catalyst contains a mesoporous carrier and acid ions loaded on the mesoporous carrier.

[0006] Preferably, the mesoporous carrier contains a first carrier and a second carrier, the first carrier is ZrO2, and the second carrier is at least one of Al2O3, SiO2, SnO2, CeO2 and TiO2.

[0007] Preferably, the acid ions are sulfate ions.

[0008] Preferably, the mass ratio of the mesoporous carrier to the acid ion is 1:(1.04-2.67).

[0009] Preferably, the polyolefin plastic is polyethylene plastic and / or polypropylene plastic.

[0010] Preferably, the method further comprises preparing the catalyst according to the following steps:

[0011] (1) mixing a precursor, citric acid, a template, hydrochloric acid and ethanol and performing a first stirring, then performing a hydrothermal reaction and performing a first drying, and then performing a first calcination to obtain the mesoporous carrier;

[0012] (2) subjecting the mesoporous carrier to a sulfation treatment and separating the solid phase for a second drying, and then subjecting the second calcination,

[0013] The precursor contains a first precursor and a second precursor, the first precursor is a zirconium source, and the second precursor is at least one of an aluminum source, a silicon source, a tin source, a cerium source and a titanium source.

[0014] Preferably, the template is P123 and / or F127.

[0015] Preferably, the concentration of the hydrochloric acid is 30wt%-38wt%.

[0016] Preferably, the mass ratio of the precursor, the citric acid, the template, the hydrochloric acid and the ethanol is (4-6) g: (0.3-0.6) g: (2-5) g: (1.5-3) g: 25 mL.

[0017] Preferably, the conditions of the hydrothermal reaction include: temperature of 70-100° C. and time of 20-30 h.

[0018] Preferably, the first calcination conditions include: temperature of 500-600° C. and time of 4-7 h.

[0019] Preferably, the second calcination conditions include: temperature of 500-600° C. and time of 4-7 h.

[0020] Preferably, the mass ratio of the catalyst to the polyolefin plastic is (0.5-2):1.

[0021] Preferably, the sulfation treatment comprises: mixing the mesoporous carrier and sulfuric acid and performing a second stirring.

[0022] Preferably, the concentration of the sulfuric acid is 0.8-1.5 mol / L.

[0023] Preferably, the usage ratio of the mesoporous carrier and the sulfuric acid is (1.1-1.5) g: 20 mL.

[0024] Preferably, the second stirring conditions include: temperature of 25-32° C., stirring rate of 400-600 rpm, and time of 12-24 h.

[0025] Preferably, the conditions for the catalytic cracking reaction include: temperature of 260-320° C. and time of 1-72 h.

[0026] Compared with the prior art, the method of the present invention uses a solid superacid catalyst to achieve catalytic degradation of polyolefin plastics at low temperature without the need for hydrogen and precious metals, thereby improving the conversion effect and the gasoline product (C4-C 13 ) can reach a yield of 65%, among which the selectivity of branched alkanes is as high as 90%, which provides a cost-effective and practical solution to plastic waste pollution and has great potential for implementation in industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a transmission electron microscope image of the catalyst prepared in Example 1;

[0028] Figure 2 is a low temperature nitrogen adsorption-desorption curve of the catalyst prepared in Example 1;

[0029] Figure 3 is a catalytic cycle diagram of the catalyst prepared in Example 1. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] The method for preparing branched alkanes by using polyolefin plastics of the present invention comprises: in an inert atmosphere, the polyolefin plastics are subjected to a catalytic cracking reaction under the action of a catalyst, wherein the catalyst contains a mesoporous carrier and an acid radical ion supported on the mesoporous carrier. According to the method of the present invention, the solid superacid catalyst used can stably exist in the air, is cheap and easy to synthesize, does not require the participation of co-reactants such as hydrogen and solvents, has an adjustable structure and suitable acid sites, and not only catalyzes the degradation of polyethylene under low temperature conditions (260-320° C.), but also increases the yield of hydrocarbons in the gasoline range, and also greatly improves the selectivity of branched alkanes in the gasoline product.

[0033] In the method of the present invention, in order to improve the selectivity of branched alkanes in gasoline products and the cyclic stability of the catalyst, the mesoporous carrier first carrier and the second carrier, the first carrier is ZrO2, the second carrier is at least one of Al2O3, SiO2, SnO2, CeO2 and TiO2, and more preferably contains ZrO2 and Al2O3. In some embodiments, the mesoporous carrier contains ZrO2 and Al2O3, and the mass ratio of ZrO2 to Al2O3 is 1: (0.55-0.83). In other embodiments, the mesoporous carrier contains ZrO2 and SiO2, and the mass ratio of ZrO2 to SiO2 is 1: (0.32-0.49). In other embodiments, the mesoporous carrier contains ZrO2 and SnO2, and the mass ratio of ZrO2 to SnO2 is 1: (0.81-1.23). In other embodiments, the mesoporous carrier contains ZrO2 and CeO2, and the mass ratio of ZrO2 to CeO2 is 1:(0.93-1.40). In other embodiments, the mesoporous carrier contains ZrO2 and TiO2, and the mass ratio of ZrO2 to TiO2 is 1:(0.43-0.65).

[0034] In the method of the present invention, the acid ion can be a sulfate ion. Sulfate ions make the catalyst have strong Lewis acid sites and can activate the CH bonds of polyethylene. The site can catalyze isomerization and β-fragmentation reactions, especially A-type β-fragmentation reactions; the catalyst system with adjustable structure and acid sites makes the selectivity of branched alkanes in gasoline products higher; in addition, the catalyst is stable and the S element is not easy to lose, and the catalyst can still maintain its initial performance after multiple reactions and recycling.

[0035] In the method described in the present invention, in order to improve the selectivity of branched alkanes in the gasoline product, the mass ratio of the mesoporous carrier and the acid ion is preferably 1:(1.04-2.67), more preferably 1:(1.31-2.67), for example, it can be 1:1.04, 1:1.31, 1:1.42, 1:1.59, 1:1.70, 1:1.81, 1:2.26 or 1:2.67.

[0036] In the method of the present invention, the pore size of the catalyst may be 5-10 nm, preferably 6-10 nm. The specific surface area of ​​the catalyst may be 100-150 m 2 / g, preferably 110-150m 2 / g.

[0037] In the method of the present invention, the polyolefin plastic may be polyethylene plastic and / or polypropylene plastic, preferably polyethylene plastic. The weight average molecular weight of the polyethylene plastic may be 40,000-100,000. The weight average molecular weight of the polypropylene plastic may be 80,000-100,000. Both the polyethylene plastic and the polypropylene plastic may be commercially available.

[0038] In the method of the present invention, the method may further include preparing the catalyst according to the following steps:

[0039] (1) mixing a precursor, citric acid, a template, hydrochloric acid and ethanol and performing a first stirring, then performing a hydrothermal reaction and performing a first drying, and then performing a first calcination to obtain the mesoporous carrier;

[0040] (2) subjecting the mesoporous carrier to a sulfation treatment and separating the solid phase for a second drying, and then subjecting the second calcination,

[0041] The precursor may contain a first precursor and a second precursor, wherein the first precursor is a zirconium source, and the second precursor is at least one of an aluminum source, a silicon source, a tin source, a cerium source and a titanium source, preferably containing a zirconium source and an aluminum source.

[0042] In the method of the present invention, the zirconium source may be at least one of zirconium oxychloride octahydrate, zirconium chloride and zirconium nitrate pentahydrate, preferably zirconium oxychloride octahydrate. The aluminum source may be aluminum nitrate nonahydrate and / or aluminum isopropoxide, preferably aluminum nitrate nonahydrate. The silicon source may be tetraethyl silicate and / or tetramethyl silicate, preferably tetraethyl silicate. The tin source may be tin tetrachloride pentahydrate and / or tin sulfate, preferably tin tetrachloride pentahydrate. The cerium source may be at least one of cerium nitrate hexahydrate, cerium sulfate and cerium chloride, preferably cerium nitrate hexahydrate. The titanium source may be tetraethyl titanate and / or titanium tetrachloride, preferably tetraethyl titanate.

[0043] In some embodiments, the precursor contains a zirconium source and an aluminum source, and the mass ratio of the zirconium source to the aluminum source is 1:(0.78-1.16). In other embodiments, the precursor contains a zirconium source and a silicon source, and the mass ratio of the zirconium source to the silicon source is 1:(0.43-0.65). In other embodiments, the precursor contains a zirconium source and a tin source, and the mass ratio of the zirconium source to the tin source is 1:(0.72-1.08). In other embodiments, the precursor contains a zirconium source and a cerium source, and the mass ratio of the zirconium source to the cerium source is 1:(0.90-1.34). In other embodiments, the precursor contains a zirconium source and a titanium source, and the mass ratio of the zirconium source to the titanium source is 1:(0.47-0.70).

[0044] In the method of the present invention, the template agent may be P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) and / or F127 (polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer), preferably F127.

[0045] In the method of the present invention, the concentration of the hydrochloric acid may be 30wt%-38wt%, preferably 36wt%-38wt%.

[0046] In the method described in the present invention, the mass ratio of the precursor, the citric acid, the template, the hydrochloric acid and the ethanol can be (4-6) g: (0.3-0.6) g: (2-5) g: (1.5-3) g: 25 mL, preferably (4.4-6) g: (0.3-0.5) g: (2-4) g: (1.5-2.5) g: 25 mL.

[0047] In the method of the present invention, the first stirring conditions include: the temperature can be 25-32°C, preferably 28-32°C; the stirring rate can be 400-600rpm, preferably 500-600rpm; the time can be 12-24h, preferably 20-24h.

[0048] In the method of the present invention, the conditions of the hydrothermal reaction include: the temperature can be 70-100° C., preferably 70-80° C.; the time can be 20-30 h, preferably 22-26 h.

[0049] In the method of the present invention, the first drying conditions include: the temperature can be 55-90°C, preferably 60-80°C; the time can be 20-30h, preferably 24-30h.

[0050] In the method of the present invention, the conditions of the first calcination include: the temperature may be 500-600° C., preferably 500-550° C.; the time may be 4-7 hours, preferably 5-6 hours. The first calcination is carried out in a muffle furnace.

[0051] In the method of the present invention, the second drying conditions include: the temperature can be 60-80°C, preferably 60-70°C; the time can be 20-48h, preferably 24-48h. Step (2) can also include: separating the solid phase by filtration.

[0052] In the method of the present invention, the conditions of the second calcination include: the temperature may be 500-600° C., preferably 500-550° C.; the time may be 4-7 hours, preferably 5-6 hours. The second calcination is carried out in a muffle furnace.

[0053] In the method described in the present invention, in order to improve the selectivity of branched alkanes in the gasoline product, the mass ratio of the catalyst and the polyolefin plastic is preferably (0.5-2):1, more preferably (1-2):1, and specifically can be 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1.

[0054] In the method of the present invention, in order to improve the stability of sulfur in the catalyst, the sulfation treatment preferably includes: mixing the mesoporous carrier and sulfuric acid and performing a second stirring. The concentration of the sulfuric acid can be 0.8-1.5 mol / L, preferably 1.0-1.5 mol / L. The amount ratio of the mesoporous carrier and the sulfuric acid can be (1.1-1.5) g: 20 mL, preferably (1.2-1.5) g: 20 mL. The conditions of the second stirring include: the temperature can be 25-32°C, preferably 28-32°C; the stirring rate is 400-600 rpm, preferably 500-600 rpm; the time can be 12-24h, preferably 20-24h.

[0055] In the method of the present invention, in order to ensure the occurrence of catalytic cracking reaction, the inert atmosphere is preferably argon and / or nitrogen, more preferably argon. Preferably, the purity of the argon is 99.0wt%-99.9wt%.

[0056] In the method of the present invention, the conditions of the catalytic cracking reaction include: the temperature can be 260-320°C, preferably 280-300°C; the time can be 1-72h, preferably 24-48h. The catalytic cracking reaction can be carried out in a tank reactor.

[0057] In the method of the present invention, the method may specifically include: mixing and grinding the polyolefin plastic and the catalyst, then transferring to a tank reactor, introducing an inert atmosphere, heating to 260-320° C. and performing the catalytic cracking reaction for 1-72 hours.

[0058] In some embodiments, the method for preparing branched alkanes using polyolefin plastics of the present invention comprises:

[0059] (1) mixing a precursor, citric acid, a template, hydrochloric acid with a concentration of 30 wt%-38 wt% and ethanol and stirring at 25-32° C. at a stirring rate of 400-600 rpm for 12-24 h, then performing a hydrothermal reaction at 70-100° C. for 20-30 h and drying at 55-90° C. for 20-30 h, and then calcining at 500-600° C. for 4-7 h to obtain a mesoporous carrier;

[0060] (2) mixing the mesoporous carrier with sulfuric acid having a concentration of 0.8-1.5 mol / L and stirring at 25-32° C. at a stirring rate of 400-600 rpm for 12-24 h, then separating the solid phase by filtration and drying at 60-80° C. for 20-48 h, and then calcining at 500-600° C. for 4-7 h to obtain a catalyst;

[0061] (3) mixing and grinding the polyolefin plastic and the catalyst, and then transferring them to a tank reactor, introducing an inert atmosphere, heating to 260-320° C., and performing the catalytic cracking reaction for 1-72 hours.

[0062] The precursor contains a first precursor and a second precursor, the first precursor is a zirconium source, and the second precursor is at least one of an aluminum source, a silicon source, a tin source, a cerium source and a titanium source; the mass ratio of the precursor, the citric acid, the template, the hydrochloric acid and the ethanol is (4-6) g: (0.3-0.6) g: (2-5) g: (1.5-3) g: 25 mL; the mass ratio of the mesoporous carrier and the sulfuric acid can be (1.1-1.5) g: 20 mL; the mass ratio of the catalyst and the polyolefin plastic is (0.5-2): 1.

[0063] In other embodiments, the method for preparing branched alkanes using polyolefin plastics of the present invention comprises:

[0064] (1) mixing a zirconium source, an aluminum source, citric acid, a template, hydrochloric acid with a concentration of 36 wt%-38 wt% and ethanol and stirring at 28-32° C. at a stirring rate of 500-600 rpm for 20-24 h, then performing a hydrothermal reaction at 70-80° C. for 22-26 h and drying at 60-80° C. for 24-30 h, and then calcining at 500-550° C. for 5-6 h to obtain a mesoporous carrier;

[0065] (2) mixing the mesoporous carrier with sulfuric acid having a concentration of 1.0-1.5 mol / L and stirring at 28-32° C. at a stirring rate of 500-600 rpm for 20-24 h, then separating the solid phase by filtration and drying at 60-70° C. for 24-48 h, and then calcining at 500-550° C. for 5-6 h to obtain a catalyst;

[0066] (3) mixing and grinding the polyolefin plastic and the catalyst, and then transferring them to a tank reactor, introducing an inert atmosphere, heating to 280-300° C., and performing the catalytic cracking reaction for 24-48 hours.

[0067] Among them, the mass ratio of the zirconium source and the aluminum source is 1:(0.78-1.16); the precursor contains the zirconium source and the aluminum source; the mass ratio of the precursor, the citric acid, the template, the hydrochloric acid and the ethanol is (4.4-6) g:(0.3-0.5) g:(2-4) g:(1.5-2.5) g:25 mL; the mass ratio of the mesoporous carrier and the sulfuric acid can be (1.2-1.5) g:20 mL; the mass ratio of the catalyst and the polyolefin plastic is (1-2):1.

[0068] The following examples further illustrate the method for preparing branched alkanes from polyolefin plastics of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0069] The experimental methods in the following examples are all conventional methods in the art unless otherwise specified. The experimental materials used in the following examples are all commercially available unless otherwise specified. The polyethylene plastic in the examples is purchased from Macklin, with a brand name of Macklin and a weight average molecular weight of 80,000; the polypropylene plastic in the examples is purchased from Ruixiang Plastic Chemical Co., Ltd., with a weight average molecular weight of 80,000.

[0070] Example 1

[0071] (1) 3 g F127, 2 g hydrochloric acid with a concentration of 37 wt%, 3.09 g zirconium oxychloride octahydrate, 2.40 g aluminum nitrate nonahydrate, and 0.4 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, followed by a hydrothermal reaction at 70° C. for 24 h. The obtained mixed solution was dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a mesoporous carrier;

[0072] (2) 1.23 g of the mesoporous support obtained in step (1) and 20 mL of 1 mol / L sulfuric acid were mixed and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, then the solid phase was separated by filtration and dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a catalyst (the mass ratio of the mesoporous support to sulfate ions was 1:1.59, and the mass ratio of ZrO2 to Al2O3 was 1:0.55);

[0073] (3) 0.2 g of polyethylene plastic and 0.2 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, argon gas was introduced, the temperature was raised to 300° C. and the catalytic cracking reaction was carried out for 48 hours. After the reaction was completed, it was naturally cooled to 25° C.

[0074] Example 2

[0075] (1) 4 g F127, 2.5 g hydrochloric acid with a concentration of 38 wt%, 3.09 g zirconium oxychloride octahydrate, 2.78 g cerium nitrate hexahydrate, and 0.5 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 32° C. at a stirring rate of 600 rpm for 24 h, followed by a hydrothermal reaction at 80° C. for 26 h. The obtained mixed solution was dried at 80° C. for 30 h, and then calcined at 500° C. for 6 h to obtain a mesoporous carrier;

[0076] (2) 1.30 g of the mesoporous carrier obtained in step (1) and 20 mL of 1.2 mol / L sulfuric acid were mixed and stirred at 32° C. at a stirring rate of 600 rpm for 24 h, then the solid phase was separated by filtration and dried at 70° C. for 48 h, and then calcined at 500° C. for 6 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:1.81, and the mass ratio of ZrO2 to CeO2 was 1:0.93);

[0077] (3) 0.2 g of polyethylene plastic and 0.16 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, introduced with argon, heated to 280° C. and subjected to the catalytic cracking reaction for 24 h. After the reaction was completed, the mixture was naturally cooled to 25° C.

[0078] Example 3

[0079] (1) 2 g F127, 1.5 g hydrochloric acid with a concentration of 36 wt%, 3.09 g zirconium oxychloride octahydrate, 1.33 g tetraethyl silicate, and 0.3 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 28° C. at a stirring rate of 500 rpm for 22 h, followed by a hydrothermal reaction at 70° C. for 22 h. The obtained mixed solution was dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a mesoporous carrier;

[0080] (2) 1.10 g of the mesoporous carrier obtained in step (1) and 20 mL of 1.5 mol / L sulfuric acid were mixed and stirred at 32° C. at a stirring rate of 500 rpm for 24 h, then the solid phase was separated by filtration and dried at 70° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:1.04, and the mass ratio of ZrO2 to SiO2 was 1:0.32);

[0081] (3) 0.2 g of polyethylene plastic and 0.3 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, argon gas was introduced, the temperature was raised to 280° C. and the catalytic cracking reaction was carried out for 48 hours. After the reaction was completed, it was naturally cooled to 25° C.

[0082] Example 4

[0083] (1) 3 g F127, 2 g hydrochloric acid with a concentration of 37 wt%, 3.09 g zirconium oxychloride octahydrate, 1.46 g tetraethyl titanate, and 0.4 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, followed by a hydrothermal reaction at 70° C. for 24 h. The obtained mixed solution was dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a mesoporous carrier;

[0084] (2) 1.15 g of the mesoporous carrier obtained in step (1) and 20 mL of 1 mol / L sulfuric acid were mixed and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, then the solid phase was separated by filtration and dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:1.70, and the mass ratio of ZrO2 to TiO2 was 1:0.43);

[0085] (3) 0.2 g of polyethylene plastic and 0.2 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, introduced with argon, heated to 280° C. and subjected to the catalytic cracking reaction for 48 h. After the reaction was completed, the mixture was naturally cooled to 25° C.

[0086] Example 5

[0087] (1) 3 g F127, 2 g hydrochloric acid with a concentration of 37 wt%, 3.09 g zirconium oxychloride octahydrate, 2.24 g tin tetrachloride pentahydrate, and 0.4 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, followed by a hydrothermal reaction at 70° C. for 24 h. The obtained mixed solution was dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a mesoporous carrier;

[0088] (2) 1.50 g of the mesoporous carrier obtained in step (1) and 20 mL of 1 mol / L sulfuric acid were mixed and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, then the solid phase was separated by filtration and dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:1.31, and the mass ratio of ZrO2 to SnO2 was 1:0.81);

[0089] (3) 0.2 g of polyethylene plastic and 0.2 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, introduced with argon, heated to 280° C. and subjected to the catalytic cracking reaction for 48 h. After the reaction was completed, the mixture was naturally cooled to 25° C.

[0090] Example 6

[0091] (1) 6 g F127, 3 g hydrochloric acid with a concentration of 38 wt%, 2.58 g zirconium oxychloride octahydrate, 3.00 g aluminum nitrate nonahydrate, and 0.6 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 32° C. at a stirring rate of 600 rpm for 12 h, followed by a hydrothermal reaction at 100° C. for 20 h. The obtained mixed solution was dried at 90° C. for 20 h, and then calcined at 600° C. for 4 h to obtain a mesoporous carrier;

[0092] (2) 1.3 g of the mesoporous carrier obtained in step (1) and 20 mL of 1.5 mol / L sulfuric acid were mixed and stirred at 32° C. at a stirring rate of 600 rpm for 12 h, then the solid phase was separated by filtration and dried at 80° C. for 20 h, and then calcined at 600° C. for 4 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:2.26, and the mass ratio of ZrO2 to Al2O3 was 1:0.83);

[0093] (3) 0.2 g of polyethylene plastic and 0.4 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, introduced with argon, heated to 320° C. and subjected to the catalytic cracking reaction for 12 h. After the reaction was completed, the mixture was naturally cooled to 25° C.

[0094] Example 7

[0095] (1) 4 g P123, 1.5 g hydrochloric acid with a concentration of 30 wt%, 2.9 g zirconium oxychloride octahydrate, 2.6 g aluminum nitrate nonahydrate, and 0.3 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 25° C. at a stirring rate of 400 rpm for 24 h, followed by a hydrothermal reaction at 70° C. for 30 h. The obtained mixed solution was dried at 55° C. for 30 h, and then calcined at 500° C. for 7 h to obtain a mesoporous carrier;

[0096] (2) 1.5 g of the mesoporous carrier obtained in step (1) and 20 mL of 0.8 mol / L sulfuric acid were mixed and stirred at 25° C. at a stirring rate of 400 rpm for 24 h, then the solid phase was separated by filtration and dried at 60° C. for 48 h, and then calcined at 500° C. for 7 h to obtain a catalyst (the mass ratio of the mesoporous carrier to sulfate ions was 1:1.04, and the mass ratio of ZrO2 to Al2O3 was 1:0.64);

[0097] (3) 0.2 g of polyethylene plastic and 0.1 g of the catalyst obtained in step (2) were mixed and ground, then transferred to a kettle reactor, introduced with argon, heated to 260° C. and subjected to the catalytic cracking reaction for 72 h. After the reaction was completed, the mixture was naturally cooled to 25° C.

[0098] Example 8

[0099] The method of Example 1 is followed, except that the polyethylene plastic is replaced by polypropylene plastic.

[0100] Example 9

[0101] The method of Example 1 was followed, except that the polyethylene plastic was replaced with recycled powder of polyolefin plastic (the gloves and plastic bags made of PE material were dried at 80° C. and then ground).

[0102] Comparative Example 1

[0103] (1) 3 g F127, 2 g hydrochloric acid with a concentration of 37 wt%, 3.09 g zirconium oxychloride octahydrate, 2.40 g aluminum nitrate nonahydrate, and 0.4 g citric acid were sequentially added into a conical flask containing 25 mL of anhydrous ethanol and stirred at 28° C. at a stirring rate of 500 rpm for 20 h, followed by a hydrothermal reaction at 70° C. for 24 h. The obtained mixed solution was dried at 60° C. for 24 h, and then calcined at 550° C. for 5 h to obtain a mesoporous carrier;

[0104] (2) 0.2 g of polyethylene plastic and 0.2 g of the mesoporous carrier obtained in step (1) were mixed and ground, then transferred to a kettle reactor, argon gas was introduced, the temperature was raised to 280° C. and the catalytic cracking reaction was carried out for 48 hours. After the reaction was completed, it was naturally cooled to 25° C.

[0105] Test Example 1

[0106] The catalyst prepared in Example 1 was characterized by transmission electron microscopy. The test method was based on the national standard GB / T 17507. Figure 1 As shown, it can be seen that the catalyst prepared in Example 1 has an obvious mesoporous structure.

[0107] The catalyst prepared in Example 1 was subjected to a low-temperature nitrogen adsorption and desorption test. The test method was based on the national standard GB / T 5211-2008. Figure 2 As shown, it can be seen that the catalyst prepared in Example 1 is a mesoporous material. The average pore size and specific surface area of ​​the catalyst prepared in Example 1 are recorded in Table 1.

[0108] The catalysts prepared in Examples 2-7 were also subjected to transmission electron microscopy characterization and low-temperature nitrogen adsorption-desorption tests. The results were similar to those in Example 1 and are not described in detail. The measured average pore size and specific surface area of ​​the catalysts are recorded in Table 1.

[0109] Test Example 2

[0110] The gaseous products after the reaction of Examples 1-9 and Comparative Example 1 were collected by air bags for qualitative and quantitative analysis by gas chromatography. At the same time, 2 mL of dichloromethane was added to the autoclave reactor, and then centrifuged at a speed of 10000 rpm for solid-liquid separation. The separated liquid products were subjected to qualitative and quantitative tests by gas chromatography-mass spectrometry and gas chromatography. The test method was based on the national standard GB / T 30431-2020. The solid products were dried at 120°C for 24 h, and the plastic conversion rate, branched alkane selectivity and gasoline (C4-C 13 ) yield and recorded in Table 2, the calculation formula is: plastic conversion rate = ((initial plastic mass - remaining plastic mass) / initial plastic mass), branched alkane selectivity = gasoline (C4-C 13 ) mass of branched alkanes / gasoline (C4-C 13 ) quality, gasoline (C4-C 13 ) yield = (gasoline (C4-C 13 ) mass / (initial plastic mass-remaining plastic mass)).

[0111] Stability test

[0112] 0.2g of the catalyst prepared in Example 1 and 0.2g of polyethylene plastic were mixed and ground, and then the obtained mixture was placed in a kettle reactor, argon was introduced, the temperature was raised to 280°C, and the catalytic cracking reaction was carried out for 48 hours. After the reaction was completed, it was naturally cooled to 25°C. The gaseous products after the reaction were collected with air bags for qualitative and quantitative analysis by gas chromatography. At the same time, 2mL of dichloromethane was added to the kettle reactor, and then the liquid was taken out and centrifuged at a speed of 10000rpm for solid-liquid separation. The separated liquid product was subjected to qualitative and quantitative testing by gas chromatography-mass spectrometry and gas chromatography. The test method was based on the national standard GB / T30431-2020. The separated solid product was dried at 120°C for 12 hours, and the plastic conversion rate was calculated. The solid product separated each time was calcined at 550 degrees Celsius for 3 hours. The above operation was repeated 4 times for catalytic cracking of polyethylene plastic, and the plastic conversion rate was recorded. Figure 3 .

[0113] from Figure 3 It can be seen that according to the method for preparing branched alkanes using polyolefin plastics of the present invention, the catalyst can still maintain its initial performance after multiple reactions, recycling and regeneration.

[0114] Herein, the mass ratio of the mesoporous carrier and sulfate ions in the catalysts in Examples 1-7 and the composition ratio of the mesoporous carrier were measured by inductively coupled plasma (ICP) testing, and the testing method was based on the national standard GB / T 13747.26-2022.

[0115] Table 1

[0116] serial number Average pore size (nm) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 9.4 115 Example 2 8.2 110 Example 3 9.6 125 Example 4 9.8 128 Example 5 6.8 108 Example 6 9.0 120 Example 7 9.4 124

[0117] It can be seen from the results in Table 1 that the catalyst of the present invention has a mesoporous structure and a large specific surface area.

[0118] Table 2

[0119]

[0120] It can be seen from the results in Table 2 that Examples 1-9 using the method for preparing branched alkanes from polyolefin plastics of the present invention have higher gasoline yields, plastic conversion rates and branched alkanes selectivity.

[0121] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing branched alkanes using polyolefin plastics, characterized in that: The method comprises: in an inert atmosphere, subjecting polyolefin plastic to a catalytic cracking reaction under the action of a catalyst, The catalyst contains a mesoporous carrier and acid ions loaded on the mesoporous carrier.

2. The method according to claim 1, characterized in that The mesoporous carrier contains a first carrier and a second carrier, the first carrier is ZrO2, and the second carrier is at least one of Al2O3, SiO2, SnO2, CeO2 and TiO2.

3. The method according to claim 1 or 2, characterized in that: The acid ions are sulfate ions.

4. The method according to any one of claims 1 to 3, characterized in that: The mass ratio of the mesoporous carrier to the acid ion is 1:(1.04-2.67).

5. The method according to any one of claims 1 to 4, characterized in that: The polyolefin plastic is polyethylene plastic and / or polypropylene plastic.

6. The method according to any one of claims 3 to 5, characterized in that: The method further comprises preparing the catalyst according to the following steps: (1) mixing a precursor, citric acid, a template, hydrochloric acid and ethanol and performing a first stirring, then performing a hydrothermal reaction and performing a first drying, and then performing a first calcination to obtain the mesoporous carrier; (2) subjecting the mesoporous carrier to a sulfation treatment and separating the solid phase for a second drying, and then subjecting the second calcination, The precursor comprises a first precursor and a second precursor, the first precursor is a zirconium source, and the second precursor is at least one of an aluminum source, a silicon source, a tin source, a cerium source and a titanium source; Preferably, the template is P123 and / or F127; Preferably, the concentration of the hydrochloric acid is 30wt%-38wt%; Preferably, the mass ratio of the precursor, the citric acid, the template, the hydrochloric acid and the ethanol is (4-6) g: (0.3-0.6) g: (2-5) g: (1.5-3) g: 25 mL; Preferably, the conditions of the hydrothermal reaction include: temperature of 70-100°C and time of 20-30h; Preferably, the first calcination conditions include: temperature of 500-600°C and time of 4-7h; Preferably, the second calcination conditions include: temperature of 500-600° C. and time of 4-7 h.

7. The method according to any one of claims 1 to 6, characterized in that: The mass ratio of the catalyst to the polyolefin plastic is (0.5-2):

1.

8. The method according to claim 6 or 7, characterized in that: The sulfation treatment comprises: mixing the mesoporous carrier and sulfuric acid and performing a second stirring; Preferably, the concentration of sulfuric acid is 0.8-1.5 mol / L; Preferably, the usage ratio of the mesoporous carrier and the sulfuric acid is (1.1-1.5) g: 20 mL.

9. The method according to claim 8, characterized in that The second stirring conditions include: temperature of 25-32° C., stirring rate of 400-600 rpm, and time of 12-24 h.

10. The method according to any one of claims 1 to 9, characterized in that: The conditions of the catalytic cracking reaction include: temperature of 260-320° C. and time of 1-72 h.